The North-South gap in overweight and obesity in England. - Scarborough, P; Allender, S (2008)
Regional differences in overweight and obesity levels in England have mirrored those of CVD, with higher levels in the North. It is unclear whether the increase in the prevalence of overweight and obesity over the last 15 years has been consistent in different regions of the country. BMI data from each of the health surveys for England conducted between 1993 and 2004 were analysed. Annual grouped estimates of the prevalence of overweight (BMI >/= 25 kg/m2) and obesity (BMI >/= 30 kg/m2) for the North and the South of England were produced by appropriately combining regional administrative authorities. Logistic regression analyses were performed to assess the independence of the geographical effect after adjustment for age and social class. The prevalence of both overweight and obesity in women has risen more quickly in the North than in the South between 1993 and 2004, leading to a widening of inequalities. The prevalence of both overweight and obesity in women in the South has remained reasonably stable since 1997. The prevalence rates of both conditions in men have risen in parallel in the North and the South between 1993 and 2004 by approximately 8 %. The OR for obesity for young women increased between 1993/98 and 1998/2004 from 1.07 (1.00, 1.14) to 1.21 (1.13, 1.30). Widening geographical inequalities in overweight and obesity rates in women could lead to widening inequalities in cardiovascular and other diseases.